PEMERIKSAAN KEBUGARAN IBU HAMIL - Jannah, Roikhatul; Sariana, Erna; Primasari, Nina (IFI cabang Kota Bekasi, 2024)
Health during pregnancy is one of the efforts that can be improved so that mothers can go through pregnancy and childbirth healthily. The need for fitness checks for pregnant women, because fitness checks for pregnant women is an important first step in ensuring the health of the mother and the fetus she is carrying. Based on these considerations, this community service program was developed. Objective: Efforts to check the fitness of pregnant women to ensure that pregnant women are physically and mentally ready to give birth well and safely in Jatiwarna Village, Kec. Pondok Melati Bekasi City in 2023. Method: This program carries out several activities including: preparation and coordination of activities with Posyandu cadres. Results: Implementation of the Physical Fitness examination of pregnant women in 11 RWs of Jatiwarna Subdistrict which was carried out at the Huma Akasia Posyandu on Saturday 3 June 2023, the number of pregnant women participating was 51 pregnant women with gestational ages in the 2nd trimester and 3rd trimester, carrying out this examination activity the pregnant women were accompanied by each posyandu cadre. Conclusion: Community service activities were carried out well.